(untitled) (Bangladesh Agronomy Journal, 2025)
Various weed management practices including physical, mechanical, biological and chemical methods are commonly applied by the farmers. Of all possible weed control practices, use of chemicals (herbicides) stands first and a large number of herbicide groups having different mode of actions are commonly used. However, considering the effectiveness and safe use with eco-toxicological aspect, it is important to finalize the optimum dose before application to the farmer’s fields. An experiment was conducted at the research field of Agronomy Division, Joydebpur, Gazipur during the Kharif-1 season of 2017 and Rabi 2017-2018 to find out the optimum rate of herbicide (CLIO) to control weeds in maize field for getting higher yield. Six treatments viz., i) CLIO @35 mL ha−1, ii) CLIO @55 mL ha−1, iii) CLIO @75 mL ha−1, iv) CLIO @95 mL ha−1, v) CLIO @115 mL ha−1 and vi) control were tested on maize (cv. BARI Hybrid maize-9). Herbicides were sprayed at 10 Days After Sowing (DAS) according to treatments. Weed samples were taken at 25 and 45 DAS. Major weeds flora were Bathua (Chenopodium album), Durba (Cynadon dactylon), Anguli (Digitaria sanguinalis), Helencha (Jussica repens), Hatishur (Heliotropium indicum), Shama (Echinochloa crusgalli), Bangchora, Swetlomy (Gnaphalium japonicum), Mutha (Cyperus rotundus), Shaknote (Amaranthus viridis), Gaicha (Paspalum commersonii), Chapra (Eleusine indica), Bon Masur (Vicia sp.). Weed dry matter weight significantly varied in different treatments. Weed relative density were highest in no weeding in both Kharif-I, 2017 and Rabi 2017-18. The highest dry weight of weeds at 25 DAS (14.15 g m−2) and (15.16 g m−2) and at 45 DAS (44.31 g m−2) and (48.37 g m−2), respectively in Kharif-1, 2017 and Rabi 2017-18 were found in control plot whereas the lowest in spraying of CLIO @115 gm m−2 both at 25 and 45 DAS. The maximum weed control efficiency (WCE) over control both at 25 DAS (84.95% in Kharif-, 2017 and 89.95% in Rabi 2017-18) and at 45 DAS (80.48% in Kharif-I, 2017 and 89.45% in Rabi 2017-18), respectively in spraying of CLIO @115 mL ha−1. The maximum grain yield both in Kharif-I, 2017(9.77 t ha−1) and Rabi 2017-18 (9.51 t ha−1) was found in spraying of CLIO @115 mL ha−1 which was statistically identical with spraying of CLIO @75 mL ha−1 and 95.00 mL ha−1 and lowest in no weeding. The highest marginal benefit–cost ratio (MBCR) both in Kharif-1, 2017 (2.28) and Rabi 2017-18 (2.41) was observed in spraying of CLIO @95 mL ha−1 and lowest in no weeding. Results revealed that application of CLIO @ 95 mL ha−1 at 10 DAS of maize is economical viable, and it needs further trial to investigate eco-toxicological consequences to environment and living organisms after application. Bangladesh Agron. J. 2024, 27(1): 1-8